1995
DOI: 10.1016/0009-9236(95)90055-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cisplatin on urinary thromboxane B2 excretion*

Abstract: Purpose Thromboxane A2 (TxA2) is implicated in the pathogenesis of various forms of drug‐induced renal damage. Based on previous functional studies, we postulated that cis‐dichlorodiammineplatinum (cisplatin) induces intrarenal TxA2 synthesis. To test this hypothesis, we measured urinary excretion of thromboxane B2 (TxB2), the stable inactive metabolite of TxA2, during and after cisplatin administration. Patients and methods The study included 16 patients with malignant disease who were scheduled to receive ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…These results are in good agreement with those of previous reports [22,23]. Several reports demonstrate different mechanisms involved in the CDDP-induced nephrotoxicity including protein kinase C activation [24], elevation of caspase-3 activity resulting in renal cell apoptosis [25], enhancement of intrarenal synthesis of thromboxane A 2 [26] and dyslipidemia [27].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in good agreement with those of previous reports [22,23]. Several reports demonstrate different mechanisms involved in the CDDP-induced nephrotoxicity including protein kinase C activation [24], elevation of caspase-3 activity resulting in renal cell apoptosis [25], enhancement of intrarenal synthesis of thromboxane A 2 [26] and dyslipidemia [27].…”
Section: Discussionsupporting
confidence: 82%
“…Cisplatin has been used as a chemotherapeutic agent for the treatment of bladder cancer (32), but its use is associated with renal toxicity (33) and increased renal synthesis of thromboxane A 2 (34,35). Increased intrarenal synthesis of TP has been shown to be associated with impaired function (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it was reported that urinary excretion of TXB 2 was increased 4.5-fold during and immediately after cisplatin infusion in patients treated for various malignancies. 31 TXA 2 production was also observed following treatment with other cytotoxic drugs such as gentamicin 32 and cyclosporine. 33 This further supports the clinical relevance of our findings and implies that not only might a defective TP-Siva axis contribute to apoptosis resistance in tumours, but a functional TP-Siva axis in surrounding normal tissues and organs might also contribute to the toxicity of the chemotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 92%